ZmEXPB7, a β-expansin gene, contributes to drought tolerance in Arabidopsis - Xiong, Jing; Wang, Xianqiu; Ye, Xueling; Liu, Changying; Han, Jialiang (Frontiers in Genetics, 2025)
Drought stress poses a significant threat to maize productivity, highlighting the need to elucidate molecular mechanisms underlying drought tolerance. Previous studies identified ZmLBD33 as a regulator of drought stress responses that interacts with the cell wall-loosening gene ZmEXPB7. To elucidate the function of ZmEXPB7 in drought tolerance, we conducted heterologous expression studies in Arabidopsis. The results demonstrated that ZmEXPB7 expression was rapidly induced under PEG6000-simulated stress, reaching peak levels within 1 h. Overexpression of ZmEXPB7 in Arabidopsis significantly enhanced drought tolerance, improved root growth, and increased survival rates under osmotic and soil drought conditions. Transgenic plants exhibited reduced water loss, decreased stomatal density, and enhanced stomatal closure. DAB and NBT staining demonstrated that the ROS accumulated in ZmEXPB7-overexpressed Arabidopsis. A physiological index assay also revealed that SOD and POD activities in ZmEXPB7-overexpressed Arabidopsis were lower than those in wild-type Arabidopsis. These findings indicate that ZmEXPB7 positively regulates drought tolerance by modulating stomatal aperture and H2O2 signaling. This study highlights the crucial role of expansin genes in stress adaptation and positions ZmEXPB7 as a potential target for engineering drought-resilient crops.